2022
DOI: 10.3390/su14148228
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Multiple Forest Service Based on the Integration of Stand Structural Attributes in Mixed Oak Forests

Abstract: In order to understand forest services at stand level through the integration of structural attributes, forest structures in three main stand types were analyzed based on various structural attributes relating to the services of habitat conservation, timber production and soil water conservation in Loess Plateau, China. Forty sample plots with similar site and environment conditions were established in three types of oak stands. Twenty-two indexes such as stand density, mean DBH, mean height, etc., were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…While the values of mixed broad-leaved forest and mixed coniferous broadleaved forest are affected not only by the difference in volume growth of age groups, but also by the proportion of tree species due to their complex compositions. Therefore, the forest type is closely linked to the ecological service value (Guan et al, 2022). The growth rate of each tree species at different age stages determined the growth of the forest, and although the DBH growth curves of the 10 primary tree species studied demonstrated that the growth rate gradually declined with an increase in DBH, it remains affected by species-specific factors (Lee et al, 2004;Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While the values of mixed broad-leaved forest and mixed coniferous broadleaved forest are affected not only by the difference in volume growth of age groups, but also by the proportion of tree species due to their complex compositions. Therefore, the forest type is closely linked to the ecological service value (Guan et al, 2022). The growth rate of each tree species at different age stages determined the growth of the forest, and although the DBH growth curves of the 10 primary tree species studied demonstrated that the growth rate gradually declined with an increase in DBH, it remains affected by species-specific factors (Lee et al, 2004;Chen et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…in soil macrofauna is still limited. [4,10,[14][15][16][17]. Amazonas et al [18] evaluated the density and diversity of soil macrofauna during the tropical forest restoration period in southeastern Brazil.…”
Section: Introductionmentioning
confidence: 99%